Age-and sex-specific burden of cardiovascular disease attributable to 5 major and modifiable risk factors in 10 asian countries of the western pacific region - Huxley, Rachel; Hirakawa, Y.; Hussain, M.; Aekplakorn, W.; Wang, X.; Peters, S.; Mamun, A.; Woodward, M. (2015)
Cardiovascular disease (CVD) is the leading cause of mortality worldwide, causing an estimated 18 million deaths annually. Much of the burden of CVD resides in lower-and middle-income countries, particularly those Asian countries comprising the Western Pacific Region. Epidemiological studies have convincingly shown that up to 90% of all CVD can be explained by a small number of modifiable risk factors, including blood pressure, smoking, diabetes, total cholesterol and excess body weight. However, the relationship between these risk factors and coronary artery disease and stroke often differ by age and sex, and yet these differences are often overlooked in burden of disease estimations. As such, that can result in either an over-or under-estimation of the disease burden in specific population subgroups, which may affect resource allocation of healthcare. In this review, we derive the most reliable and previously unpublished estimates of the age-and sex-specific burden of vascular disease attributable to the aforementioned risk factors for 10 of the most populous Asian countries in the Western Pacific Region. Understanding how the burden of vascular disease is distributed within and between populations is crucial for developing appropriate health policies and effective treatment strategies, particularly in resource-poor settings.